Liberal Feminism in Nawal El Saadawi’s Memoirs of A Woman Doctor (2000) - Putri Amalia Zahra; Tri Murniati; Ririn Kurnia Trisnawati (English Literature Studi Program Universitas Islam Makassar, 2023)
This article is entitled Liberal Feminism in Nawal El Saadawi’s Memoirs of A Woman Doctor (2000). It aims to reveal the struggles of the nameless character to fight against patriarchal practices portrayed in the novel. This exploration used a qualitative descriptive method in analyzing data. The data of this study were obtained from narratives and conversations from the novel Memoirs of a Woman Doctor by Nawal El Sadaawi. Taking Rosemary Tong’s three aspects of liberal feminism as the lens, this study found that the nameless main character achieves equality in education by becoming a doctor, equality in economy by having her own income, and equality in civil liberties by speaking her mind freely.